Aloesin Suppresses Cell Growth and Metastasis in Ovarian Cancer SKOV3 Cells through the Inhibition of the MAPK Signaling Pathway. (18th June 2017) - Zhang, Li-qian; Lv, Rong-wei; Qu, Xiang-dong; Chen, Xian-jun; Lu, Hong-sheng; Wang, Ying
Abstract : Aloesin is an active constituent of the herb aloe vera and plays a crucial role in anti-inflammatory activity, ultraviolet protection, and antibacterium. We investigated the role and possible mechanisms of aloesin in the cell growth and metastasis of ovarian cancer. It was found that aloesin inhibited cell viability and cell clonality in a dose-dependent manner. It arrests the cell cycle at the S-phase and induced apoptosis in SKOV3 cells. In an in vivo experiment, it was observed that aloesin inhibited tumor growth. Moreover, it inhibited migration and invasion of cancer in SKOV3 cells. Interestingly, members from the mitogen-activated protein kinase (MAPK) signaling family became less phosphorylated as the aloesin dose increased. This suggests that aloesin exerts its anticancer effect through the MAPK signaling pathway. Our data also highlights the possibility of using aloesin as a novel therapeutic drug for ovarian cancer treatment.